Favouring modulation of circulating lipoproteins and lipid loading capacity by direct antiviral agents grazoprevir/elbasvir or ledipasvir/sofosbuvir treatment against chronic HCV infection. Issue 7 (14th June 2017) - Sun, Hung-Yu; Cheng, Pin-Nan; Tseng, Chiung-Ying; Tsai, Wei-Jen; Chiu, Yen-Cheng; Young, Kung-Chia
Abstract : Objective: Lipid homoeostasis is disturbed in patients with HCV infection. Direct-acting antiviral agent (DAA) treatment eradicates chronic HCV viraemia, but the dynamics of lipid components remain elusive. This study investigates the clinical manifestation and mechanistic relevance of plasma triglyceride (TG), cholesterol (Chol), lipoproteins and apolipoproteins (apos) after DAA treatment. Design: Twenty-four patients with chronic genotype 1 (GT1) HCV treated with elbasvir/grazoprevir or ledipasvir/sofosbuvir for 12 weeks, and followed-up thereafter, were recruited. Their TG, Chol, apoAI and apoB levels were quantified in plasma samples and individually fractionated lipoprotein of various classes. Liver fibrosis was evaluated using the FIB-4 Score. The TG and Chol loading capacities were calculated with normalisation to apoB, which represents per very low density lipoprotein (VLDL) and LDL particle unit Results: DAA treatment achieved a sustained virological response rate of 91.7% and reduced the FIB-4 Score. Relative to the baseline, the plasma TG level was reduced but the Chol level increased gradually. Plasma apoB levels and apoB/apoAI ratio were transiently downregulated as early as the first 4 weeks of treatment. The TG and Chol loading capacities in VLDL were elevated by ~20% during the period of DAA treatment and had steadily increased by 100% at follow-up. Furthermore, the TG-to-Chol ratio in VLDL was increased, while the ratio in LDL was reduced, indicating an efficient catabolism. Conclusion: The DAA treatment of patients with chronic hepatitis C might lead to efficient HCV eradication and hepatic improvement concomitantly evolving with favouring lipoprotein/apo metabolisms.